SIGNIFIKANSI IMPLEMENTASI KONSEP EKONOMI ISLAM DALAM TRANSAKSI BISNIS DI ERA MODERN - Toha Andiko (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2017)
Abstract: The thinking of Islamic economics in Indonesia today, is still limited to the theme of banking or financial institutions. The lack of development of Islamic economic concepts is still happening in terms of macro and microeconomics as well as systems in Islamic statistics and accounting. Implementation of Islamic economic system is expected to serve as a guide in state government, in building a prosperous society both materially and spiritually. In addition, Shariabased Islamic economics is expected to be a solution to economic underdevelopment, and to change the dominant capitalist and communist system over the years. Islamic economics is believed to save people morality from materialismhedonism, and can unite Muslims to jointly achieve falah (prosperity) in general. The significance of sharia-based Islamic economics is evident in the sharia bank’s increasingly potential business offering services compared to conventional banks. Implementation of Islamic economics on muamalah activities can also be felt in the positive role of Islamic banks and on-bank syariah financial institutions that encourage the development of the real sector, this can be seen from the start of increasing the portion of the contract for the results of mudharabah and musyarakah and other transactions.